2018
DOI: 10.1039/c8nj03521k
|View full text |Cite
|
Sign up to set email alerts
|

Computational biochemical investigation of the binding energy interactions between an estrogen receptor and its agonists

Abstract: We present the energy profiles of estrogen receptor–agonist ligand interactions in atomic detail using a quantum biochemical approach.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 70 publications
0
6
0
Order By: Relevance
“…However, it is well-known that the length and intensity in each of these interactions presents a range that can be slightly higher or shorter depending on the angle formed and the atoms involved. Therefore, to properly evaluate the coupling of the ligands, we perform a search for an optimal binding site radius, adding the individual interaction energies of those amino acid residues within imaginary spheres with a pocket radius r centered at the ligand, according to ref .…”
Section: Resultsmentioning
confidence: 99%
“…However, it is well-known that the length and intensity in each of these interactions presents a range that can be slightly higher or shorter depending on the angle formed and the atoms involved. Therefore, to properly evaluate the coupling of the ligands, we perform a search for an optimal binding site radius, adding the individual interaction energies of those amino acid residues within imaginary spheres with a pocket radius r centered at the ligand, according to ref .…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, we characterize the ligands as L , and the amino acid residue that interacts with the ligands as R i , with i indicating the index of amino acid residue i -th. The cap C i ( C i * ) is structured by the neighboring residue covalently bonded to the amine group (carboxyl) of the residue R i through the protein chain, providing a better description of its electronic environment. , For these fragmented structures, energy calculations based on DFT were performed, and the interaction energy between the ligand and the individual fragment, IE MFCC ( L – R i ), was calculated according to .25ex2ex normalI E MFCC ( L R i ) = E ( L C i R i C i * ) E ( C i R i C i * ) infix− E ( L C i C i * ) + E ( C i C i * ) , where the first term, E ( L – C i R i C i * ), corresponds to the total energy of the system composed of the binder and the capped residue; the second term, E ( C i R i C i * ), is the total energy of the residue with caps; the third term, E ( L – C i C i * ), is the total energy of the system formed by the caps and the ligand; the fourth and last term, E ( C i C i * ), is the energy of caps with the dangling bonds passivated by hydrogen. Furthermore, in this strategy, water molecules contained in the crystallographic structure were explicitly considered in the calculation, being associated with residue R i or one of its caps when a hydrogen bond (H-bond) is formed between them.…”
Section: Methodsmentioning
confidence: 99%
“…To analyze the changes in the investigated complexes upon DNA binding, not only MM, as with estradiol and DNA [125], but also MD has been applied [126]. The latter study identified specific bases within the aptamer (short-stranded DNA/RNA, binds only specific molecules [127]) and demonstrated the importance of water-mediated hydrogen bonds in the aptamer-estradiol complex.…”
Section: Quantitative Structure-activity Relationship (Qsar)mentioning
confidence: 99%